Analysis of Inspiratory Minute Volume (mVi) and Expiratory Minute Volume (mVe) Parameter Measurement using Flow Analyzer Design with Volume Control Ventilation (VCV) Mode on Ventilator - Wakidi, Levana Forra; Farid Amrinsani (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
The Flow Analyzer Ventilator functions as a breathing aid by controlling the volume of air provided to the patient. In VCV mode, the ventilator regulates a fixed volume of inspiration for each patient's breath. To ensure that the ventilator functions according to its specifications, accurate measurements of the Inspiratory Minute Volume (mVi) and Expiratory Minute Volume (mVe) parameters are required. Flow analyzers play an important role in this research as a tool to measure and verify the output produced by ventilators. This research focuses on the manufacture of a flow analyzer to measure and evaluate two important parameters, namely mVi and mVe, on ventilators operating in VCV mode. Data collection was carried out using VCV mode and was carried out 5 times with tidal volume settings of 200mL, 300mL, 400Ml, 500mL, and 600ml as well as with an I:E ratio of 1:2 and a PEEP pressure of 5cmH2O. Based on the available data, the Minute Volume Expiratory (MVE) parameter showed the highest error in the 300 mL tidal volume setting with a value of -14.7%. After the module was adjusted, the 600 mL tidal volume setting had an average error of 0.69 with a standard deviation of 1.351, while the 200 mL setting recorded the lowest average error of -0.12. Adjustments to the module and manual calculations resulted in more accurate information, suggesting that lower tidal volume settings, such as 200 mL, may improve measurement accuracy on the ventilator. Overall, this study indicates that while higher volume settings can increase data variation, lower settings can provide more consistent and accurate measurement results.The use of the AFM 3000 sensor on the Flow Analyzer is proven to be used in measuring airflow on ventilators.